2022
DOI: 10.1097/md.0000000000030171
|View full text |Cite
|
Sign up to set email alerts
|

Ligamentum flavum hypertrophy significantly contributes to the severity of neurogenic intermittent claudication in patients with lumbar spinal canal stenosis

Abstract: Ligamentum flavum hypertrophy (LFH) is a known contributor to lumbar spinal canal stenosis (LSCS). However, the clinical significance and quantitative role of LFH compared to other components, such as disc bulging and facet hypertrophy, have not yet been examined. We investigated the correlation between the quantitative radiological factors, clinical symptoms, and outcomes in patients with LSCS. In total, 163 patients diagnosed with single-level (L4-L5) stenosis were included. The patients were divided into 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…On the other hand, the symptoms are relieved by forward exion, sitting, or recumbence. It is recently postulated that in ammatory changes contribute to LF hypertrophy, or that in ammation by itself causes neurogenic claudication's and pain [11][12][13]. In our study histological changes of LF are investigated in two different groups after which proposition for new mechanism of neurogenic claudication's was obtained.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, the symptoms are relieved by forward exion, sitting, or recumbence. It is recently postulated that in ammatory changes contribute to LF hypertrophy, or that in ammation by itself causes neurogenic claudication's and pain [11][12][13]. In our study histological changes of LF are investigated in two different groups after which proposition for new mechanism of neurogenic claudication's was obtained.…”
Section: Introductionmentioning
confidence: 95%
“…13 Regarding the mechanism of the dynamic component of LSS, several articles have reported that posture-induced or axial pressure-induced elastic deformation of LF was the main contributor. [14][15][16][17][18][19][20][21] Lumbar extension or standing position may cause two adjacent laminas to move closer, followed by LF thickening and infolding. By contrast, lumbar flexion or lying flat position may cause the two-adjacent lamina to separate, resulting in the stretching and thinning of LF as well as the disappearance of LF infolding.…”
Section: Dynamic Components Of Lssmentioning
confidence: 99%
“…In contrast, the venous stasis theory suggests that a combination of low levels of oxygen and metabolite buildup are responsible due to venous backup at the cauda equina. It is recently postulated that inflammatory changes contribute to LF hypertrophy, or that inflammation by itself causes neurogenic claudication's and pain [7][8][9] . In our study histological changes of LF are investigated in two different groups after which proposition for new mechanism of neurogenic claudication's was obtained.…”
mentioning
confidence: 99%